Hubungan Penerapan Rekam Medis Elektronik Dengan Manajemen Risiko Keselamatan Pasien Di Puskesmas X Kota Malang - Oktavianingsih Setyawulandari; Restu Ayu Eka Pustika Dewi; Dwi Nur Siti Marchamah (Indonesian Journal of Health Community, 2025)
Electronic medical records is inseparable from issues related to patient safety risk management. The X Primary Health Center, which has implemented electronic medical records, has still experienced patient safety incidents. The purpose of this study is to determine the relationship between the implementation of electronic medical records and patient safety risk management. The results of the study showed that the implementation of electronic medical records was in accordance with the six indicators for the organization of electronic medical records and the implementation of patient safety risk management met five out of four indicators in the risk management scope and five items of patient safety goals. The indicator that was not met was the risks associated with the service facility. The Spearman rank correlation test result was 1.00, with a significance value (2-tailed) of 0.000, which is positive, meaning there is a significant, positive correlation between the implementation of electronic medical records and patient safety risk management at the X Primary Health Center. The study suggests that the maintenance of electronic medical records should be carried out outside of service hours and efforts should be made to meet the required resources.